Síntese de fotocatalizadores suportados em zeólita do tipo NaX utilizando Nb, Zn, e Fe para o tratamento de efluentes por processo oxidativo avançado - Fernanda de Freitas Brites Nóbrega (2015)
Industrial wastewaters usually show high concentrations of recalcitrant components and are greatly toxic. Advanced Oxidation Processes (AOP), particularly heterogeneous photocalysis, have been considered as feasible alternatives for industrial wastewater treatment. The use of solar energy as energy source for the conversion of photons into chemical energy arises as the ideal way to treat these wastewaters. Currently, most studies regarding photocatalysis have focused on nano-structured oxides usually doped with metals and other oxides in order to increase their activating energy. However, photocatalysts are traditionally applied in suspension, which restricts their use in industrial scale for wastewater treatment. In the present work, niobium, zinc and iron in the ratio of 10 and 15% (m/m) were supported in NaX zeolites through wet impregnation so as to obtain photocatalysts with high oxidative potential under solar radiation. TG analysis was performed in order to validate the temperature required for oxide formation and calcination for active phase generation. Analysis showed that zeolite’s BET surface area was reduced significantly after the formation of niobium pentoxide, zinc oxide and goethite. Also, impregnation method and calcination process has favored the formation of niobium pentoxides on zeolites’ surface which shows an activating energy, band gap, equals 2,9eV. Goethite supported zeolites also showed band gap equals 2,9eV. ZnO/NaX structure was an exception for that its electronic structure was not modified. Heating process optimization during the synthesis of Nb2O5/NaX in the tubular reactor achieved an improvement of its photocatalytic activity from 40% to 75% dye mineralization under visible radiation in the same reaction conditions. It is possible to assume that heating process influences on the formation of more active photocatalysts. Pure zeolite has adsorbed 67% of methylene blue in 24 hours. After oxides impregnation, however, adsorption rate decreased with an increase on impregnated oxides. Optimum doses of supported photocatalysts used in the reaction was found to be 5g/L. Nb2O5/NaX and β-FeOOH/NaX were the photocatalysts which showed best results on dye degradation using UV-Vis and visible radiation. Nb2O5/NaX and β-FeOOH/NaX were selective to adsorption of drugs: ofloxacine, flumequine and ibuprofen. KEY WORDS: